Ultrasonographic Halo Score in giant cell arteritis: association with intimal hyperplasia and ischaemic sight loss. (23rd December 2020) - van der Geest, Kornelis S. M.; Wolfe, Konrad; Borg, Frances; Sebastian, Alwin; Kayani, Abdul; Tomelleri, Alessandro; Gondo, Prisca; Schmidt, Wolfgang A.; Luqmani, Raashid; Dasgupta, Bhaskar
Abstract: Objectives: We investigated the relationship between the ultrasonographic Halo Score and temporal artery biopsy (TAB) findings in GCA. Methods: This is a prospective study including 90 patients suspected of having GCA. Ultrasonography of temporal/axillary arteries and a TAB were obtained in all patients at baseline. An experienced pathologist evaluated whether TAB findings were consistent with GCA, and whether transmural inflammation, giant cells and intimal hyperplasia were present. Ultrasonographic Halo Scores were determined. Receiver operating characteristic analysis was performed. Results: Twenty-seven patients had a positive TAB, while 32 patients with a negative TAB received a clinical diagnosis of GCA after 6 months of follow-up. Patients with a positive TAB showed higher Halo Scores than patients with a negative TAB. The presence of intimal hyperplasia in the biopsy, rather than the presence of transmural inflammation or giant cells, was associated with elevated Halo Scores in patients with GCA. The Halo Score discriminated well between TAB-positive patients with and without intimal hyperplasia, as indicated by an area under the curve of 0.82 in the receiver operating characteristic analysis. Patients with a positive TAB and intimal hyperplasia more frequently presented with ocular ischaemia (40%) than the other patients with GCA (13–14%). Conclusion: The ultrasonographic Halo Score may help to identify a subset of GCA patients with intimal hyperplasia, a TAB feature associated with ischaemic sight loss.